Barriers to Reciprocity Communication between Superiors and Subordinates when Working From Home - Afifah Aini Bahran Harahap; Leila Mona Ganiem (CV. Inara, 2021)
Work from Home (WFH) is currently a popular term on social media, especially after the government officially urges businesses to assign employees to work from home. The appeal is related to efforts to reduce the spread of the Covid-19 outbreak. Against this background, the researcher conducted a study to see how reciprocal communication between superiors and subordinates occurs and how obstacles occur when working from home at PT Indonesia Comnets Plus (ICON+). This study uses the Post-Positive Paradigm and uses the Single Case method with a qualitative descriptive approach and research data obtained from interviews and observations and documentation. The research location was carried out at ICON+ in the Jakarta area. Managers and VPs are classified as superiors, while officers and staff are classified as subordinates. The results showed that the reciprocal communication between superiors and subordinates was dominated by using the written method. Communication barriers that occur between superiors and subordinates at ICON+ include semantic disruption, structural disruption, and behavioral disruption. The research findings say that the biggest obstacle experienced by superiors and subordinates at ICON+ is the frame of mind barrier, namely the difference in perception when the communication process occurs between superiors and subordinates. The overall communication barrier is more often experienced by subordinates than superiors.